ENHANCING OMANI UNIVERSITY STUDENTS’ WRITING AND STUDY SKILLS: DISCUSSION FORUM MODULE - Ginosyan, Hranush; Tuzlukova, Victoria (Indonesian Journal of Applied Linguistics, 2015)
Abstract: This paper reports the results of a study conducted among first-year Foundation Program English Language (FPEL) students, English teachers and FPEL course coordinators at Sultan Qaboos University (SQU) in Oman with the aim to examine the use of Moodle forums for advancing writing and study skills of the students in higher level FPEL courses by participating in asynchronous discussions, interacting with other students and/or the teacher, and exchanging ideas by posting comments. In addition, students’, teachers’ and course coordinators’ perceptions about the discussion forum as an activity in an e-learning environment that can successfully contribute to FPEL curriculum writing and study skills goals and teaching approaches were examined with regard to the attainment of learning outcomes (LOs). Data were collected by interviewing teachers and course coordinators, conducting an online survey for students, monitoring students’ participation in forum activities and analyzing the policy documents related to writing and study skills components of FPEL 0560 course. The results of the study corroborate some significant findings of the previous work in the field, and clearly demonstrate that Moodle forums support writing fluency, allow students more time for developing ideas and working on their writing and study skills’ assignments. Additionally, forums foster a sense of purpose and community, as well as contribute to communication skills’ development of language learners through online language learning environment by responding to online assignments, inviting feedback, commenting on/grading other students’ comments, seeking and providing help with purposes of enhancing, reinforcing and researching.